POLA ASUH ORANG TUA DAN PERILAKU SELF-HARM PADA REMAJA: STUDI DESKRIPTIF - Kusumawati, Henny; Wetik, Syenshie Virgini (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2026)
Introduction: Self-harm among adolescents has become an increasingly complex and concerning mental health phenomenon, along with rising psychological, social, and academic pressures during this developmental stage. This behavior not only reflects impaired emotion regulation but also represents an expression of psychological distress that is not adaptively channeled. Particularly parenting styles, plays an important role in shaping adolescent vulnerability and psychological resilience. Objective: To identify the description of parenting styles and Self-harm behavior among adolescents. Method: This study used a quantitative descriptive design with a survey approach. The population consisted of 120 students, while the respondents are 91 were those identified as having experienced Self-harm. Result: 91 students (75.83%) reported having engaged in Self-harm. Based on severity, most were in the low category, 68 students (74.73%), followed by the moderate category with 20 students (21.98%), and the high category with 3 students (3.29%). Respondents who had engaged in Self-harm most commonly experienced permissive parenting from both fathers and mothers, totaling 48 students (52.75%). Conclusion: The prevalence of Self-harm among adolescent is relatively high and is most commonly found among those raised with permissive parenting styles. This highlights the important role of parenting in emotional regulation and the prevention of Self-harm behavior.